Structure, Function and Performance of the Financial Services Sector in Zimbabwe since 1980 - Chirisa, Innocent; Manungo, Godfrey; Mpahlo, Rumbidzai; Ndhlovu, Faith (Lighthouse: The Zimbabwe Ezekiel Guti University Journal of Law, Economics and Public Policy, 2024)
This article diagnoses and discusses the structure, function and performance of the financial services sector in Zimbabwe since 1980. It adopted a document review approach. An extensive literature scanning from reports, plans, statutes and statutory instruments was done. It made use of thematic analysis to understand and assess the financial service sector in Zimbabwe during the post-colonial era to date. The financial sector in Zimbabwe has gone through various economic policy regimes since independence in April 1980. After it attained independence during this first decade, Zimbabwe‘s financial sector was still relatively small and dominated by foreign institutions. The country has experienced financial repression and high financing costs have discouraged domestic investment. High real interest rates continue to limit private credit growth, despite low financial intermediation due to lack of effective competition and a high level of non-performing loans. While the effects of mild, periodic financial repression on growth are ambiguous, there is adequate evidence that large negative interest rates cannot be sustained and are eventually leading to reduced growth. Therefore, there is need for an efficient financial system that enhances a country‘s growth prospects by channelling resources to their most productive uses, thereby fostering a more efficient allocation of resources. It also helps boost aggregate saving and investment rates, thus speeding up the accumulation of physical capital. Finally, growth is enhanced by strengthening competition and stimulating innovative activities, promoting dynamic efficiency.